EFEKTIVITAS MODEL PEMBELAJARAN OPEN ENDED DENGAN MEDIA POWER POIN PADA MATERI LINGKARAN DAN BANGUN RUANG KUBUS DAN BALOK - ., Suminto (JURNAL E-DUMATH, 2016)
The studentsâ math achievement in the second grade of the SMP Negeri 3Pringsewu is not effective, even though, in learning process, the teacherhas involved the students actively and give broad chance to students togain more knowledge. From those condition, alternative learning isneeded by using the open ended learning model with the power pointpresentation. This research used descriptive research. Researcher usedobservation sheet they were teacherâs ability sheet, activityâs studentsheet, respondâs student sheet, then to get studentsâ learning achievementwere used essay. Based on the data analysis of open ended learningprocess with power point presentation toward the subject of circle,square, and rectangle. It can be concluded that the result was effective. Itcan be seen in the teacherâs ability was 83%, studentsâ activity was77,4%, studentsâ response was 84,2% and the number of the studentsachieves the effective learning about 79,48%.Keywods: open ended learning model, effectiveness in learning